Implementasi Pelestarian Kearifan Lokal pada Mata Pelajaran Sosiologi Melalui Kegiatan P5 Berbasis Contextual Learning - Astika, Fina Aulia; Prahita, Bagas Narendra; Budiati, Atik Catur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The practice of local wisdom was chosen because it was seen that students' interest in literacy was declining so that it affected their knowledge of local wisdom in their disciplines. This study aims to identify and analyze the implementation of increasing awareness of local wisdom based on contextual learning from P5 local wisdom and identify and analyze the impact for students regarding the implementation of increasing awareness of local wisdom based on contextual learning from P5. This research uses qualitative research methods with phenomenological research type. Phenomenology aims to find and explore more deeply the human experience of self and life. Data were collected through observation, interview, and communication. The results showed that the school was able to implement P5 practices with the main objective of raising awareness of the importance of local wisdom. Attention to the suitability of learning outcomes in sociology subjects is the main basis for implementing P5 practices. Habituation has occurred from the practice of P5 activities, namely by students conducting research into local wisdom objects around the school. Cooperation carried out by sociology teachers and P5 coordinators in determining essential material in sociology subjects. This research uses Pierre Bourdieu's habitus theory to see the practice of habituation from the arena. The school environment becomes an arena in the habituation process. The school has capital so that activities run smoothly from economic capital, cultural capital, social capital, and symbolic capital. In addition to capital, the school has agents, namely the local wisdom P5 team and sociology teachers. The agent has a strategy of choosing social research to be essential material in P5 local wisdom and students practice and learn outside of school directly in the community. The production is by students making a report on local wisdom P5 activities and P5 activities published in online media. The habituation process of P5 local wisdom activities can increase awareness about the need to maintain and preserve local wisdom.